Characterization of Olive Seed Powder Incorporated Low Density Polyethylene Composites - Sibel Tuna; İbrahim Şen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Global warming, increasing production and consumption rates, environmental concerns have revealed the need for some innovative material studies, and studies on the use of polymeric composites prepared with natural based fillers have become widespread in order to increase environmental awareness and ensure sustainable production. Composite materials prepared by using easily accessible, affordable, lightweight, high-strength plant based fillers can be used in many areas. In this study, composites of low density polyethylene (LDPE), which is one of the most widely used thermoplastics, were prepared by injection moulding process using the waste seeds of olives (OS), which have an important place in Turkey's agriculture and economy, and the density, hardness (Shore D), spectroscopic (Fourier transform infrared (FTIR) spectroscopy), morphological (Scanning electron microscopy (SEM)), mechanical, thermal (Differential Scanning Calorimetry (DSC), Heat Deflection Temperature (HDT) and Vicat softening temperature) analyses of OS filled LDPE composites were performed. As a result of the study, an increase in hardness and elastic modulus values of OS filled LDPE composites was observed, while no noticeable decrease in thermal properties was seen.